The IVP New Testament commentary : Ephesians - Liefeld, Walter L. (Downers Grove, Illinois. IVP Academic., 1997)
"More than any other book of the Bible, Ephesians displays the great purpose and plan of God for the church," Walter Liefeld writes. "It provides a perspective that is unique: God's--and the believer's--view from the 'heavenly realms.'"For those who long to delve into the mind and purposes of God, few books are more helpful than Paul's letter to the Ephesians. Here the apostle paints in broad strokes the great plan of God for his church, centered on its head, Jesus Christ, and living out its calling in praise of God's glory. Beginning with doxology, Paul calls on the church to support its words of praise with deeds to match. Christians today will find here inspiration and insight that will confirm their allegiances and shape their lives.
Introduction -- Outline of Ephesians -- Commentary.
Includes bibliographical references (pages 173-178).
Keywords: Bible. -- Commentaries